Peramalan Volatilitas IHSG dan Estimasi Value-at-Risk Menggunakan Model Student APARCH - Najibullah, Najibullah; Ariansyah, Ricky; Rizky, Fitrian (HEI EMA : Jurnal Riset Hukum, Ekonomi Islam, Ekonomi, Manajemen dan Akuntansi, 2023)
This study aim to find the best model to predict daily volatility of IHSG using APARCH model under student-t distribution, estimate value-at-risk measure based on the model and compare it with the value-at-risk measure estimated from GARCH. This study limits the search only on APARCH model class. The sample are IHSG dataset which is derived from yahoo finance, starting from Jan 1st, 2015 to Dec 31th, 2021. The result suggest that value-at-risk measure estimated using student APARCH are more adept to negatif shock than that of GARCH. Nevertheless, the result of value-at-risk back-testing do not show any significant differences between those two.